2010
DOI: 10.1002/adfm.201000763
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Exciton and Polaron Dynamics in Phosphorescent Dye Blended Polymer Photovoltaic Devices

Abstract: The triplet exciton and polaron dynamics in phosphorescent dye (PtOEP) blended polymer (MEH‐PPV) photovoltaic devices are investigated by quasi‐steady‐state photo‐induced absorption (PIA) spectroscopy. According to the low‐temperature PIA and photoluminescence (PL) results, the increase in strength of the triplet‐triplet (T1‐Tn) absorption of MEH‐PPV in the blend system originates from the triplet‐triplet energy transfer from PtOEP to MEH‐PPV. The PtOEP blended MEH‐PPV/C60 bilayer photovoltaic device shows a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Yu et al reported that the exciton diffusion distance was increased by doping (t-bt) 2 Ir(acac) into copper phthalocyanine (CuPc) [21]. However, Lee reported that carrier generation in the bulk heterojunction was not enhanced in the presence of PtOEP because the rate and probability of excition dissociation between PtOEP and PCBM are much faster and higher than that of triplet-triplet energy transfer between PtOEP and MEH-PPV [26]. Zhang et al reported that the PCE of PSCs based on oleic acid-Fe 3 O 4 -doped P3HT:PCBM as the active layer was enhanced by ∼18% primarily due to the increase of sc , which is attributed to the increase of the population of triplet excitons induced by the magnetic field effect originated from the superparamagnetism of Fe 3 O 4 nanoparticles (NPs) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al reported that the exciton diffusion distance was increased by doping (t-bt) 2 Ir(acac) into copper phthalocyanine (CuPc) [21]. However, Lee reported that carrier generation in the bulk heterojunction was not enhanced in the presence of PtOEP because the rate and probability of excition dissociation between PtOEP and PCBM are much faster and higher than that of triplet-triplet energy transfer between PtOEP and MEH-PPV [26]. Zhang et al reported that the PCE of PSCs based on oleic acid-Fe 3 O 4 -doped P3HT:PCBM as the active layer was enhanced by ∼18% primarily due to the increase of sc , which is attributed to the increase of the population of triplet excitons induced by the magnetic field effect originated from the superparamagnetism of Fe 3 O 4 nanoparticles (NPs) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Triplet excitons in organic semiconductors are strongly bound and localized electron-hole pairs that have total electronic spin of one. Diffusion of triplet excitons plays a key role in organic optoelectronic devices: generation of triplet excitons in solar cells using phosphorescent dopants or the process of exciton fission may double the internal quantum efficiency [1,2]. Manipulation of triplet excitons toward phosphorescent emission in light emitting diodes leads to a fourfold increase in the device efficiency [3][4][5].…”
mentioning
confidence: 99%
“…26 increase in triplet excitons was observed for the halogen-containing derivatives due to an increased rate of ISC, the porphyrin derivatives used in this study showed a decrease in photoactivity. 24 In a recent report, the quantum efficiency of a pentacene containing organic solar cell was greatly enhanced by using a triplet exciton blocking poly(3-hexylthiophene) layer. 50,51 The triplet excited state energy of free-base tetraphenylporphyrins is approximately 1.5 eV.…”
Section: Preliminary Bhj Device Studiesmentioning
confidence: 99%
“…[13][14][15][16][17][18] To increase the probability of exciton dissociation, interfaces must lie within the exciton diffusion length (typically between 10 -20 nm for many organic semiconductors). [18][19][20][21] Alternatively, enhancing the singlet to triplet exciton conversion yield in the photoactive layer has been shown to increase photoconversion efficiency of organic solar cells, [22][23][24] presumably due to longer triplet exciton diffusion lengths. [18][19][20][21] Alternatively, enhancing the singlet to triplet exciton conversion yield in the photoactive layer has been shown to increase photoconversion efficiency of organic solar cells, [22][23][24] presumably due to longer triplet exciton diffusion lengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation